Metabotropic Glutamate Receptor 5 in Natural Killer Cells Attenuates Liver Fibrosis by Exerting Cytotoxicity to Activated Stellate Cells. Issue 4 (29th July 2021) - Choi, Won‐Mook; Ryu, Tom; Lee, Jun‐Hee; Shim, Young‐Ri; Kim, Myung‐Ho; Kim, Hee‐Hoon; Kim, Ye Eun; Yang, Keungmo; Kim, Kyurae; Choi, Sung Eun; Kim, Won; Kim, Seok‐Hwan; et al.
Abstract : Background and Aims: The important roles of glutamate and metabotropic glutamate receptor 5 (mGluR5) in HSCs have recently been reported in various liver diseases; however, the mechanism linking the glutamine/glutamate metabolism and mGluR5 in liver fibrosis remains unclear. Here, we report that mGluR5 activation in natural killer (NK) cells attenuates liver fibrosis through increased cytotoxicity and interferon‐γ (IFN‐γ) production in both mice and humans. Approach and Results: Following 2‐week injection of carbon tetrachloride (CCl4 ) or 5‐week methionine‐deficient and choline‐deficient diet, liver fibrosis was more aggravated in mGluR5 knockout mice with significantly decreased frequency of NK cells compared with wild‐type mice. Consistently, NK cell–specific mGluR5 knockout mice had aggravated CCl4 ‐induced liver fibrosis with decreased production of IFN‐γ. Conversely, in vitro activation of mGluR5 in NK cells significantly increased the expression of anti‐fibrosis‐related genes including Ifng, Prf1 (perforin), and Klrk1 (killer cell lectin like receptor K1) and the production of IFN‐γ through the mitogen‐activated extracellular signal‐regulated kinase/extracellular signal‐related kinase pathway, contributing to the increased cytotoxicity against activated HSCs. However, we found that the uptake of glutamate was increased in activated HSCs, resulting in shortage of extracellular glutamate and reduced stimulation of mGluR5 in NK cells. Consequently, this could enable HSCs to evade NK cell cytotoxicity in advanced liver fibrosis. In vivo, pharmacologic activation of mGluR5 accelerated CCl4 ‐induced liver fibrosis regression by restoring NK cell cytotoxicity. In humans, mGluR5 activation enhanced the cytotoxicity of NK cells isolated from healthy donors, but not from patients with cirrhosis with significantly reduced mGluR5 expression in NK cells. Conclusions: mGluR5 plays important roles in attenuating liver fibrosis by augmenting NK cell cytotoxicity, which could be used as a potential therapeutic target for liver fibrosis.